Effects of Formaldehyde Inhalation on Zinc, Copper and Iron Concentrations in Liver and Kidney of Male Rats - Ozen, Oguz Aslan; Kus, Ilter; Bakirdere, Sezgin; Sarsilmaz, Mustafa; Yaman, Mehmet (Humana Press Inc, 2011)
In the present study, adult Wistar albino male rats were exposed to formaldehyde at different periods (subacute and subchronic) and concentrations (5.0 and 10.0 ppm) in order to figure out the changes in the concentration of Zn, Cu and Fe. It was observed that the formaldehyde inhalation caused gradual decline of body weights in the experimental groups when compared with control groups. It was found that subacute (4-week) or subchronic (13-week) exposure to formaldehyde for rats may cause growth retardation. After inhalation procedure, concentration of copper, zinc and iron were determined in liver and kidney tissues of rats using atomic absorption spectrophotometer. In addition, concentrations of Cu, Zn and Fe changed by the effect of formaldehyde in subacute and subchronic groups.
Keywords: Formaldehyde; Liver; Kidney; Zinc; Copper; Iron